2003
DOI: 10.1080/03014460310001616473
|View full text |Cite
|
Sign up to set email alerts
|

Utility of different body composition indicators: demographic influences and associations with blood pressures and heart rates in adolescents (Heartfelt Study)

Abstract: RMI, impedance or skinfold estimators are necessary for research requiring an accurate description of body composition changes during adolescence and for assessing the role of lean and fat tissue in disease aetiology. A 2-skinfold method is just as effective as the more complicated impedance. Mid-body circumferences are closely related to blood pressures and heart rates, suggesting their importance as indicators of abdominal fat in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…WHtR has been shown to be a simple, noninvasive, and practical tool that correlates well with visceral fat (32). Both WC and WHtR have been found to be indicators of high abdominal fat mass and powerful markers associated with a number of cardiovascular risk factors and metabolic syndrome in epidemiologic studies (30)(31)(32). Statistically significant differences were found for weight, height, WC, and WHtR among the underweight, normal, overweight, and obese groups in the present study.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…WHtR has been shown to be a simple, noninvasive, and practical tool that correlates well with visceral fat (32). Both WC and WHtR have been found to be indicators of high abdominal fat mass and powerful markers associated with a number of cardiovascular risk factors and metabolic syndrome in epidemiologic studies (30)(31)(32). Statistically significant differences were found for weight, height, WC, and WHtR among the underweight, normal, overweight, and obese groups in the present study.…”
Section: Discussionsupporting
confidence: 57%
“…WC is easy to determine and is a useful measurement of fat distribution in children and adolescents (31). WC may be useful to characterize a population in terms of abdominal fat distribution and to determine the prevalence of risk factors and also in clinical practice to determine response to weight control measures in children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, there are only a few data regarding which is the best available marker of obesity in relation to BP. [17][18][19][20][21] Finally, office blood pressure (OBP) that is classically used for the evaluation of hypertension in children and adolescents may lead to misinterpretation of the true BP. 22 Recently, it has been shown that home blood pressure (HBP) monitoring is an applicable and more reliable method for the evaluation of BP in children.…”
Section: Introductionmentioning
confidence: 99%
“…Body mass index (BMI) is the most commonly used indirect measure of overall adiposity (Bose and Mascie-Taylor, 1997;Bhadra et al, 2001;Ghosh et al, 2001Ghosh et al, , 2003Ghosh et al, , 2004Bose and Mukhopadhyay, 2004), while percent body fat (PBF), fat mass (FM), fat free mass (FFM), and fat mass index (FMI) are the most widely studied measures of body composition (VanItalie et al, 1990;Wang and Bachrach, 1996;Bose, 1998;Mueller et al, 2003). Prediction of PBF from skinfold thicknesses is an acceptable method for the assessment of body composition in children and adolescents (Deurenberg et al, 1990;Williams et al, 1992;Mueller et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Prediction of PBF from skinfold thicknesses is an acceptable method for the assessment of body composition in children and adolescents (Deurenberg et al, 1990;Williams et al, 1992;Mueller et al, 2003).…”
Section: Introductionmentioning
confidence: 99%